A Systematic Summary of Systematic Reviews on the Topic of Hip Arthroscopic Surgery. Issue 9 (19th September 2018) - de SA, Darren; Lian, Jayson; Sheean, Andrew J.; Inman, Kathleen; Drain, Nicholas; Ayeni, Olufemi; Mauro, Craig
Background: There is a rapidly growing body of literature on the topic of hip arthroscopic surgery. Purpose: To provide an overall summary of systematic reviews published on the indications, complications, techniques, outcomes, and information related to hip arthroscopic surgery. Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review of all hip arthroscopic surgery–related systematic reviews published between January 2000 and May 2018 was performed using PubMed, MEDLINE, and the Cochrane Library. Narrative reviews and non-English articles were excluded. Results: A total of 837 articles were found, of which 85 met the inclusion criteria. Included articles were summarized and divided into 6 major categories based on the subject of the review: femoroacetabular impingement (FAI), non-FAI indications, surgical technique, outcomes, complications, and miscellaneous. Conclusion: A summary of systematic reviews on hip arthroscopic surgery can provide surgeons with a single source for the most current synopsis of the available literature. As the prevalence of orthopaedic surgeons performing hip arthroscopic surgery increases, updated evidence-based guidelines must likewise be advanced and understood to ensure optimal patient management.